2019
DOI: 10.1371/journal.pone.0222403
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biomarkers of sepsis identified by novel time-lapse proteomics of patient serum

Abstract: Serum components of sepsis patients vary with the severity of infection, the resulting inflammatory response, per individual, and even over time. Tracking these changes is crucial in properly treating sepsis. Hence, several blood-derived biomarkers have been studied for their potential in assessing sepsis severity. However, the classical approach of selecting individual biomarkers is problematic in terms of accuracy and efficiency. We therefore present a novel approach for detecting biomarkers using longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 39 publications
1
23
0
Order By: Relevance
“…Flow cytometric analysis of samples was performed in all COVID-19 patients (days 1–3, 4–7, 8–11, and 12–15) and in CINS patients (days 1–3) as previously described ( 33 , 34 ). ALC was profoundly depressed in COVID-19 patients over the entire duration of the study compared with nonseptic patients (first comparison days 1–3; P = 0.01) ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow cytometric analysis of samples was performed in all COVID-19 patients (days 1–3, 4–7, 8–11, and 12–15) and in CINS patients (days 1–3) as previously described ( 33 , 34 ). ALC was profoundly depressed in COVID-19 patients over the entire duration of the study compared with nonseptic patients (first comparison days 1–3; P = 0.01) ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
“…There have been many efforts to determine patient immune endotype using genomic or proteomic biomarkers of immunity ( 34 , 35 ). While these methods have been helpful in predicting outcomes in sepsis and other disorders ( 36 , 37 ), in general they have either not been able to provide an accurate assessment of the functional state of host immunity, as it varies over time, or have been used to determine response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis constitutes a highly heterogeneous syndrome of complex pathophysiology. The underlying immunological alterations that include pro-inflammatory, anti-inflammatory and immunosuppressive components 12 are reflected in septic plasma protein composition and varies over time according to disease severity 37 . Thus, plasma represents a favoured biological sample to search for biochemical signals that provide information on the physiological state at a given time.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the classical approaches the plasma samples are subjected to depletion of abundant proteins 23 and /or fractionation to identify individual biomarkers 37,38 which requires more analysis time, specific equipment and higher costs.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is increased in the sepsis patient group, indicating a response to inflammation and tissue damage [ 14 ]. Similarly, Hayashi et al, who studied the patient proteome over time, showed a significant decrease in haemoglobin beta 1 and 2 chains in the group of patients who did not survive sepsis [ 36 ]. These molecules could be markers of sepsis severity.…”
Section: Mass Spectrometry For the Identification Of Sepsis Biomarmentioning
confidence: 99%